To solve the quadratic equation \( 49x^2 = -392x - 784 \) using the perfect square trinomial pattern, let's first rewrite the equation in standard form:
\[ 49x^2 + 392x + 784 = 0 \]
Next, we can see if we can express the left-hand side as a perfect square. Notice that we can factor out 49 from the first two terms:
\[ 49(x^2 + 8x) + 784 = 0 \]
Now, let's complete the square for the expression inside the parentheses:
-
Take half of the coefficient of \( x \) (which is 8) and square it: \[ \left(\frac{8}{2}\right)^2 = 4^2 = 16 \]
-
Add and subtract this square inside the parentheses: \[ 49(x^2 + 8x + 16 - 16) + 784 = 0 \] \[ 49((x + 4)^2 - 16) + 784 = 0 \]
-
Distribute the 49: \[ 49(x + 4)^2 - 784 + 784 = 0 \] \[ 49(x + 4)^2 = 0 \]
Now, divide both sides by 49: \[ (x + 4)^2 = 0 \]
Taking the square root of both sides gives: \[ x + 4 = 0 \]
Therefore, solving for \( x \) gives: \[ x = -4 \]
So, the solution to the equation is: \[ \boxed{-4} \]